Acute Consumption of Prebiotic Galacto-Oligosaccharides Increases Iron Absorption from Ferrous Fumarate, but not from Ferrous Sulfate and Ferric Pyrophosphate: Stable Iron Isotope Studies in Iron-Depleted Young Women. Issue 9 (21st July 2020) - Jeroense, Frederike M D; Zeder, Christophe; Zimmermann, Michael B; Herter-Aeberli, Isabelle
ABSTRACT: Background: Although acute consumption of high doses of prebiotic galacto-oligosaccharides (GOS) increases fractional iron absorption (FIA) from ferrous fumarate (FeFum), it is uncertain if low doses of GOS have this effect. Furthermore, whether GOS improve iron absorption from other commonly used iron compounds and whether ascorbic acid (AA) enhances the effect of GOS on iron absorption from FeFum is unclear. Objectives: In iron-depleted women [serum ferritin (SF) <30 μg/L], we assessed: 1 ) whether the acute enhancing effect of GOS on FeFum is dose dependent; 2 ) if GOS would affect FIA from ferrous sulfate (FeSO4 ) or ferric pyrophosphate (FePP); and 3 ) if AA and GOS given together enhance FIA from FeFum to a greater extent compared with GOS alone. Methods: We recruited 46 women (mean age 22.0 y, mean BMI 21.3 kg/m 2, median SF 17.1 μg/L), and measured FIA from 14 mg iron labeled with stable isotopes in the following conditions: 1 ) FIA from FeFum given with 3.5 g, 7 g GOS, and without GOS; 2 ) FIA from FeSO4 and FePP given with and without 15 g GOS; and 3 ) FIA from FeFum given with 7 g GOS with and without 93 mg AA. FIA was measured as erythrocyte incorporation of stable isotopes after 14 d. Comparisons were made using paired samples t -test or Wilcoxon rank sum test where appropriate. Results: Giving 7 g of GOS significantly increased FIA from FeFum (+26%; P = 0.039), whereas 3.5 g GOS did not ( P = 0.130). GOS did not significantly increase FIA from FeSO4 ( P = 0.998) or FePP ( P = 0.059). FIA from FeFum given with GOS and AA was significantly higher compared with FeFum given with GOS alone (+30%; P <0.001). Conclusions: In iron-depleted women, GOS does not increase FIA from FeSO4 or FePP, but it increases FIA from FeFum. Thus, a combination of FeFum and GOS may be a well-absorbed formula for iron supplements. The study was registered at clinicaltrials.gov as NCT03762148.